2014
DOI: 10.1080/09602011.2014.922889
|View full text |Cite
|
Sign up to set email alerts
|

Visual feedback-related changes in ipsilateral cortical excitability during unimanual movement: Implications for mirror therapy

Abstract: Provision of a mirror image of a hand undertaking a motor task (i.e., mirror therapy) elicits behavioural improvements in the inactive hand. A greater understanding of the neural mechanisms underpinning this phenomenon is required to maximise its potential for rehabilitation across the lifespan, e.g., following hemiparesis or unilateral weakness. Young and older participants performed unilateral finger abductions with no visual feedback, with feedback of the active or passive hands, or with a mirror image of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
6
23
1
Order By: Relevance
“…However, there is also evidence for an ϳ25% increase in ipsilateral M1 corticospinal excitability in conjunction with viewing the isometrically contracting index finger (ϳ20% MVC) in a mirror (Garry et al 2005). The cause of the discrepant data is unclear, considering that the experimental and recording conditions were similar in two studies, one showing an increase (Garry et al 2005) and the other showing no effect (Reissig et al 2014). The insensitivity of corticospinal excitability to mirror-viewing in the present study may be related to a saturation effect.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…However, there is also evidence for an ϳ25% increase in ipsilateral M1 corticospinal excitability in conjunction with viewing the isometrically contracting index finger (ϳ20% MVC) in a mirror (Garry et al 2005). The cause of the discrepant data is unclear, considering that the experimental and recording conditions were similar in two studies, one showing an increase (Garry et al 2005) and the other showing no effect (Reissig et al 2014). The insensitivity of corticospinal excitability to mirror-viewing in the present study may be related to a saturation effect.…”
Section: Discussioncontrasting
confidence: 50%
“…However, we demonstrate uniquely that mirror-viewing of the slowly moving and contracting hand decreased SICI in the right-ipsilateral M1, suggesting that it is not the contraction itself but the visual illusion of a moving left hand that modulates SICI. In support of this, a previous study showed that mirror-viewing of isometric index finger abductions did not change ipsilateral SICI compared with no-vision and other visual feedback conditions (Reissig et al 2014); hence to create a mirror illusion and modulate SICI, it would seem the viewed image must be moving.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Interhemispheric interactions were also reported by TMS studies of unilateral movement, whereby interhemispheric inhibition and shortinterval intracortical inhibition decrease during unilateral movement (Howatson, et al, 2011;Muellbacher et al, 2000;Reissig et al, 2014;Soto, et al, 2010;Uehara et al, 2013). Therefore, we could speculate that the increase in MEP amplitudes and changes in twitch direction during late motor preparation and after movement onset in our results could be due to a decrease in interhemispheric inhibition and short-interval intracortical inhibition.…”
Section: Discussionmentioning
confidence: 45%